Analyzing Negation Markers in the Online News Article - Hermariyanti Kusumadewi; Reknosari Reknosari (STKIP PGRI Lubuklinggau, 2022)
By looking at their smart phones people automatically read what they find on the internet. People today tend to choose digital newspaper than traditional newspaper, from the economy side it is cheaper, and of course it is paperless, in short it is so much easy than reading the traditional one. There are many online newspapers that we can get easily from the internet. The focus in here is by knowing the negation markers used in Indonesian online newspapers. As reader, we can easily get the point of what the article said. Related to such problems above, the aim of the research is to analyze the negation markers in the online News. This research is conducted by using descriptive qualitative method. The data are collected from Indonesian “Jakarta Globe” Online article. Literature review and relevant research have been observed to obtain the description of the data. From the data gained, it can be concluded that the most frequently used of Negation is found in Tenses (41.18%), followed by the used of Negation in Words (39.22%), and the least is found in Modal-auxiliaries (19.61%).